Efeito de compostos inorgânicos, herbicidas e extratos foliares no desenvolvimento de microcystis aeruginosa e produção de microcistina - Tropaldi, Leandro [UNESP] (2015)
The water quality of many surface water bodies have been compromised due to occurrence of toxic cyanobacterial blooms. Many species, including Microcystis aeruginosa produce natural toxins, such as microcystins, which offer high risks to the environment and public health. Therefore, the adoption of measures to control blooms is required. This research aims to evaluate the effect of different types of substances and foliar biomass on the development of M. aeruginosa and producing microcystin-LR, in view of the need to produce information that can support blooms management programs. Effects of organic compounds, with or without known herbicide action, inorganic compounds biomass of Brazilian tree native species and green manure were evaluated on chlorophyll-α content and accumulation of microcystin-LR in M. aeruginosa. Among the tested compounds diquat, diuron and copper sulfate were most effective in reducing chlorophyll-α content and microcystin-LR accumulation. In studies with initial chlorophyll content of 0.5 mg L-1 diquat showed high potential to control M. aeruginosa at concentrations of 0.1 and 0.2 mg L-1. Diuron was more effective in reducing the total microcystin-LR content than ...